Components of the Belief-Based and Worship-Oriented Education Model in the Context of Virtual Education for Elementary School - Haleh Esfahani; Zohreh Saadatmand; Maryam Baratali (Iranian Journal of Educational Research)
Objective: The purpose of this study was to investigate the components of the belief-based and worship-oriented education model in the context of virtual education for elementary school. Methods: The method of this study is a mixed model (qualitative-qualitative) with an exploratory approach. The total research area is 53 documents, including books and articles included in reputable databases and websites in the field of religious-devotional education models and virtual education for elementary school, of which 28 were Persian documents and 25 were English documents that were indexed in reputable databases between 2004 and 2024. Data analysis in the present study was carried out using 3-stage coding. Results: The findings identified numerous components essential to a religious education model for elementary students in virtual settings. These include cognitive, cultural, and social development, as well as the growth of religious beliefs, understanding, and practices. Key skills such as communication, critical thinking, problem-solving, and cognitive abilities were highlighted. The model also emphasizes rich cultural and religious content, innovative and transformational educational methods, ethical and behavioral strategies, and effective teaching techniques like role-playing. Additionally, it stresses the importance of supervision, feedback, time management, personalization, and improving quality of life. The integration of media and digital interactions, along with fostering balanced religious and social growth, were also noted as crucial elements. Conclusions: The findings can be used by policymakers and elementary school educators in designing a faith-prayer education model for elementary school students.